2002
DOI: 10.3390/i3111117
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cytotoxicity and Gene Expression in Human Liver Carcinoma (HepG2) Cells Exposed to Arsenic Trioxide, and Monosodium Acid Methanearsonate (MSMA)

Abstract: Abstract:Research in our laboratory has demonstrated that a trivalent form of arsenic such as arsenic trioxide (AT) has the ability to cause significant cytotoxicity, and induction of a significant number of stress genes in human liver carcinoma cells (HepG 2 ). However, the literature also indicates that the toxicity of arsenic depends on its chemical form. To test this hypothesis, we further evaluated the cellular and molecular responses of HepG 2 cells following exposure to monosodium acid methanearsonate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Arsenic also insecticides, herbicides, fungicides, such as agricultural applications, rat poison, some cancer drugs, paints, wallpaper is used as wood preservatives with various items of manufacture and sheep wool, ceramic. 5 The exposure of arsenic in human is associated with cancers, organ damage and immunotoxicity. 6 Arsenic toxicity generates reactive oxygen species (ROS) such as hydroxyl radicals ( Á OH), superoxide anion (O À 2 ) through chain reactions and causes severity oxidative damage of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic also insecticides, herbicides, fungicides, such as agricultural applications, rat poison, some cancer drugs, paints, wallpaper is used as wood preservatives with various items of manufacture and sheep wool, ceramic. 5 The exposure of arsenic in human is associated with cancers, organ damage and immunotoxicity. 6 Arsenic toxicity generates reactive oxygen species (ROS) such as hydroxyl radicals ( Á OH), superoxide anion (O À 2 ) through chain reactions and causes severity oxidative damage of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…People who produce or use arsenic compounds in occupations such as nonferrous metal smelting, pesticide manufacturing and application, wood preservation, semiconductor manufacturing, or glass production can be exposed by substantially higher levels of arsenic [8,10,18,19]. As stated earlier, different species of arsenic have different degrees of toxicity, with arsine and the trivalent arsenic causing the most injury [22]. In addition to the exposure route and the arsenic species involved, the toxicity also depends on the exposure dose, frequency, duration, the biological species, age, and gender, as well as on individual susceptibilities, genetic and nutritional factors [8,16,19].…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…A review of biological properties and toxic effects of arsenic indicates that this chemical is a systemic toxicant capable of causing a significant number of health effects including: cardiovascular disease, peripheral vascular disease, developmental effects, neurologic and neurobehavioral effects, diabetes, hearing loss, portal fibrosis of the liver, lung fibrosis, hematologic effects (anemia, leukopenia, and eosinophilia), and carcinogenic effects [2,7,8,16,19,22]. Studies in Taiwan have reported that in areas where blackfoot disease is endemic, the standardized and cumulative mortality rates were significantly higher for cancer of the bladder, kidney, skin, liver, lung and colon.…”
Section: Risk Characterizationmentioning
confidence: 99%
“…Different species of arsenic have different levels of toxicity [21,22]. For example, arsenobetaine, which is the major converted form of arsenic found in various marine animals, has been shown to be relatively non-toxic [21].…”
Section: Human Health Risk Assessmentmentioning
confidence: 99%